2006
DOI: 10.1021/ja064853o
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and Zwitterionic Low-Coordinate Titanium Complexes Bearing the Terminal Phosphinidene Functionality. Structural, Spectroscopic, Theoretical, and Catalytic Studies Addressing the Ti−P Multiple Bond

Abstract: Alpha-hydrogen abstraction and alpha-hydrogen migration reactions yield novel titanium(IV) complexes bearing terminal phosphinidene ligands. Via an alpha-H migration reaction, the phosphinidene ((tBu)nacnac)Ti=P[Trip](CH(2)(tBu) ((tBu)nacnac(-) = [Ar]NC((t)Bu)CHC((t)Bu)N[Ar], Ar = 2,6-(CHMe2)(2C6H3, Trip = 2,4,6-(i)Pr3C6H2) was prepared by the addition of the primary phosphide LiPH[Trip] to the nucleophilic alkylidene triflato complex ((tBu)nacnac)Ti=CH(t)Bu(OTf), while alpha-H abstraction was promoted by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 63 publications
3
106
0
5
Order By: Relevance
“…The generality of the a-hydrogen migration [28] was further demonstrated by the synthesis of titanium(IV) phosphinidene 34 (Scheme 10 c), which bears the PNP-pincer ligand N[2-P-(CHMe 2 ) 2 -4-methylphenyl] 2 À ; imide and alkylidene functionalities can be obtained by the same approach.…”
Section: A-hydrogen Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The generality of the a-hydrogen migration [28] was further demonstrated by the synthesis of titanium(IV) phosphinidene 34 (Scheme 10 c), which bears the PNP-pincer ligand N[2-P-(CHMe 2 ) 2 -4-methylphenyl] 2 À ; imide and alkylidene functionalities can be obtained by the same approach.…”
Section: A-hydrogen Migrationmentioning
confidence: 99%
“…Analogously, Menye-Biyogo et al have reported the formation of the putative phosphinidenes 51 a from the interaction of phosphinidene complex [h 6 -pCym(Cy 3 P)Ru = P À Mes*] and alkynes by loss of the phosphine ligand. [62] Zwitterionic titanium phosphinidene 18 with its labile borate group was shown to undergo [2+2]-cycloaddition with diphenylacetylene to generate phosphatitanocyclobutene 96 (Scheme 28 a), [28] which was identified on the basis of its characteristic chemical shifts in the 31 P (d = 160.7 ppm) and 13 C NMR spectra (d = 253.5 ppm). Complex 18 was demonstrated to be able to function as a precatalyst in the catalytic hydrophosphination of PhCCPh with PhPH 2 .…”
Section: Cycloaddition To the M=p Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…[2+2]-cycloaddition, as observed for related imido complexes, then gives metallacycle 14, whose protonation with phenylphosphine yields Ti-bis(phosphido) complex 15. a-elimination would then yield the alkenylphosphine product and regenerate the catalyst [42].…”
Section: Metal-phosphinidene Intermediatesmentioning
confidence: 99%
“…The philicity is influenced by the type of spectator ligand L rather than for the nature of the transition metal M [62]. DFT [58]. These titanium(IV) phosphinidene complexes possess the shortest Ti=P bonds reported, have linear phosphinidene groups, and reveal significantly upfielded 31 P NMR chemical shifts.…”
Section: Introductionmentioning
confidence: 97%